The Effectiveness of Interactive Whiteboard Using Niesve System for Electrical Engineering Students - Zacok, Lubomir; Bernat, Milan; Pavlovkin, Jan; Dzmura, Jaroslav; Bernatova, Renata (Journal of Technical Education and Training, 2019)
The article describes possibilities of increasing the effectiveness of teaching technical subjects using an interactive whiteboard. The basic research method is a pedagogical experiment by which we compare the effectiveness of teaching in the experimental and control group. In the experimental group was used experimental teaching with the support of an interactive whiteboard (on the platform of targeted use of the virtual way of visualising the course of processes and phenomena using an interactive whiteboard overlapping the natural possibilities of other ways of visualising these processes and phenomena). The control group was teaching traditionally taught without an interactive whiteboard. Research results (based on test results) have shown that the experimental teaching system we have used during this research is more effective than the traditional teaching system. By learning with an interactive whiteboard, we found that it was easier for students to acquire new knowledge. Students were able to use the acquired knowledge to solve practical tasks.